Transforming surgical landscapes: obstacles in the integration of robotic surgery in Pakistan -is cost the only limiting factor? - Zeeshan Raza; Sabah Uddin Saqib; Hasnain Zafar; Saleem Islam (Journal of the Pakistan Medical Association, 2024)
The advantages of Robotic Assisted Surgery (RAS) over laparoscopic surgery encompass enhanced precision, improved ergonomics, shorter learning curves, versatility in complex procedures, and the potential for remote surgery. These benefits contribute to improved patient outcomes which have led to a paradigm shift in robotic surgery worldwide and it is now being hailed as the future of surgery. Robotic surgery was introduced in Pakistan in 2011, but widespread adoption has been limited. The future of RAS in Pakistan demands a strategic and comprehensive plan due to the substantial investment in installation and maintenance costs. Considering Pakistan’s status as a low to middle-income country, a well-designed economic model compatible with the existing health system is imperative. The debate over high investments in robotic surgery amid unmet basic surgical needs underscores the complex dynamics of healthcare challenges in the country. Continue...